2021
DOI: 10.3390/agronomy11081451
|View full text |Cite
|
Sign up to set email alerts
|

Softening of Processed Plant Virus Infected Cucumis sativus L. Fruits

Abstract: Texture softening of pickled cucumbers does not meet consumers’ quality expectations and leads to economic losses. The factor(s) triggering this phenomenon is still unknown. We investigated the importance of plant viruses such as Cucumber green mottle mosaic tobamovirus (CGMMV) and Zucchini yellow mosaic potyvirus (ZYMV) in the context of softening of pickles. Cucumber plants (Cucumis sativus) were infected by mechanical inoculation, grown under greenhouse conditions and tested positive for the viral infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The residual enzyme activity of fungi was not sufficient to significantly affect gherkin texture in our study. Kersten et al (2021) have already shown that pre-harvest infection with plant viruses could soften cucumbers in the jar, even though the fruits in their raw state showed no sensory texture changes apart from external conspicuousness [20]. The source of softening observed in pasteurized gherkins could therefore have a non-fungal origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual enzyme activity of fungi was not sufficient to significantly affect gherkin texture in our study. Kersten et al (2021) have already shown that pre-harvest infection with plant viruses could soften cucumbers in the jar, even though the fruits in their raw state showed no sensory texture changes apart from external conspicuousness [20]. The source of softening observed in pasteurized gherkins could therefore have a non-fungal origin.…”
Section: Discussionmentioning
confidence: 99%
“…The possible microbiological candidates contributing to gherkin softening are also the subject of science. Kersten et al (2021) showed that a Zucchini yellow mosaic virus infection of cucumber plants and fruits was associated with the softening of pasteurized gherkins, which continued to lose firmness as storage progressed [20]. Etchells et al (1958) and Raymond et al (1959) demonstrated an increased abundance of fungi on cucumber blossoms [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbit plant infections caused by a variety of viruses have the potential to cause serious problems all over the world. Fruits on virus-infected cucurbita plants are deformed and yield is reduced 2 . The ZYMV virus, a member of the Potyvirus genus, is one of the most economically significant viruses on cucurbit crops in the world 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of cucumber processing is to preserve the fruit with minimal damage. In the case of pickled cucumbers, the sensory acceptability depends on the firmness and crunchiness, which are important to consumer preferences [5]. The cucumber processing can vary according to the type of vinegar, salt content, pH value, stabilizing additives, heat treatment optimization during pasteurization, or storage temperature implemented [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of pickled cucumbers, the sensory acceptability depends on the firmness and crunchiness, which are important to consumer preferences [5]. The cucumber processing can vary according to the type of vinegar, salt content, pH value, stabilizing additives, heat treatment optimization during pasteurization, or storage temperature implemented [5]. Pickled cucumbers may be produced by direct acidification, involving the brining of fresh cucumbers in water with acetic acid and salt, followed by their pasteurization.…”
Section: Introductionmentioning
confidence: 99%